Stability of an Imperfect Truss Loaded by Wind - KRAJEWSKI, Marcin; IWICKI, Piotr (Engineering Transactions, 2016)
The present paper is devoted to the numerical research of stability of a truss loaded by wind and stiffened by elastic supports situated only at the top chord a. The lateral braces, or lateral and torsional braces were taken into account. In the research the linear buckling analysis results for the beam and shell model were presented. Two different shapes of initial geometric imperfections were considered in the non-linear static analysis performed for the shell model of the structure. As a results the truss buckling and limit load was found related to the truss bracing stiffness and the threshold bracing condition was obtained necessary to provide maximum buckling resistance of the truss.